A survey of the visual impact and community acceptance of wind farms in Australia. Issue 3 (3rd July 2020) - Lothian, Andrew
ABSTRACT: Although overall support for wind farms in Australia is strong, the rapid growth in their number and size has led to concerns about their visual impact, as evidenced by organised opposition and litigation. In March 2018, an Australia-wide Internet survey mainly of clubs and councils was conducted which asked respondents to rate the scenic quality of the landscape with and without a wind farm, and also to rate the acceptability or otherwise of the wind farm in scenes with the wind farm. Photographs of wind farms in NSW, Victoria and SA were used. From the response of nearly 800 participants a sample of 556, weighted to be representative of the Australian population, was analysed. While the respondents rated the scenic quality of landscapes with wind farms lower than scenes without them, they rated wind farms acceptable in virtually all landscapes, including high scenic quality coastal scenes. The finding suggests that the community is very tolerant of the visual impact of wind farms. Results are presented for 18 wind farms. This survey is unique in that it not only asked participants to rate the landscape with and without wind farms but it also asked them to rate the acceptability of the wind farm in each scene. To the author's knowledge, this had not been accomplished previously in Australia.